Bacterial adaptation to cold: Conservation of a short J‐domain co‐chaperone and its protein partners in environmental proteobacteria - Lana Weber; Atar Gilat; Nathanael Maillot; Deborah Byrne; Pascal Arnoux; Marie‐Thérèse Giudici‐Orticoni; Vincent Méjean; Marianne Ilbert; Olivier Genest; Rina Rosenzweig; Sébastien Dementin (Environmental Microbiology, 2023)
Bacterial genomes are a huge reservoir of genes encoding J‐domain protein co‐chaperones that recruit the molecular chaperone DnaK to assist protein substrates involved in survival, adaptation, or fitness. The atc operon of the aquatic mesophilic bacterium Shewanella oneidensis encodes the proteins AtcJ, AtcA, AtcB, and AtcC, and all of them, except AtcA, are required for growth at low temperatures. AtcJ is a short J‐domain protein that interacts with DnaK, but also with AtcC through its 21 amino acid C‐terminal domain. This interaction network is critical for cold growth. Here, we show that AtcJ represents a subfamily of short J‐domain proteins that (i) are found in several environmental, mostly aquatic, β‐ or ɣ‐proteobacteria and (ii) contain a conserved PX 7 W motif in their C‐terminal extension. Using a combination of NMR, biochemical and genetic approaches, we show that the hydrophobic nature of the tryptophan of the S. oneidensis AtcJ PX 7 W motif determines the strong AtcJ–AtcC interaction essential for cold growth. The AtcJ homologues are encoded by operons containing at least the S. oneidensis atcA , atcB , and atcC homologues. These findings suggest a conserved network of DnaK and Atc proteins necessary for low‐temperature growth and, given the variation in the atc operons, possibly for other biological functions.